Effect of Pyrolysis Temperature Variation on Optimization of Tobacco Stalk Biochar Characteristics - Kosjoko, Kosjoko; Abidin, Asroful; Hadi, Danang Kumara; Rizkina, Fitriana Dina (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2026)
Tobacco stalk waste is an agricultural residue with high potential for development as a renewable energy source through a thermochemical conversion process. This study aims to evaluate the effect of varying pyrolysis temperature on the physical and chemical characteristics of biochar produced from tobacco stalk, in order to determine the optimum temperature for producing the best quality product. The method used was a closed pyrolysis process in a stainless-steel reactor at three temperature variations: 290, 390, and 490°C for 60 minutes. The pyrolyzed biochar was analyzed using proximate analysis, calorific value testing, and chemical functional group characterization using Fourier transform infrared spectroscopy. The results showed that higher pyrolysis temperatures consistently decreased moisture and volatile matter content, while increasing the bound carbon content and calorific value of the biochar. At 490°C, the best biochar characteristics were obtained with a bound carbon content of 56.25%, a moisture content of 4.5%, volatile matter of 24.3%, and the highest calorific value reaching 5521.90 cal/g. Chemical structure analysis also indicated the formation of more stable functional groups at higher temperatures, indicating a more advanced level of carbonization. These findings indicate that within the investigated temperature range (290–490°C), 490°C yielded the biochar with the most favorable characteristics for solid fuel applications, specifically regarding fixed carbon content and calorific value. While 490°C represents the peak performance in this study, it serves as a critical operational point for achieving advanced carbonization in tobacco stalk waste. This research provides an important contribution to the development of efficient tropical biomass processing technologies. It expands the database of thermal and chemical characteristics of agricultural waste-based biochar, which has been understudied to date.